Numerical Investigation on Vortex Shedding from a Hydrofoil with a Beveled Trailing Edge - Seung-Jae Lee; Jun-Hyeok Lee; Jung-Chun Suh (Modelling and Simulation in Engineering)
To better understand the vortex shedding mechanism and to assess the capability of our numerical methodology, we conducted numerical investigations of vortex shedding from truncated and oblique trailing edges of a modified NACA 0009 hydrofoil. The hybrid particle-mesh method and the vorticity-based subgrid scale model were employed to simulate these turbulent wake flows. The hybrid particle-mesh method combines the vortex-in-cell and the penalization methods. We have implemented numerical schemes to more efficiently use available computational resources. In this study, we numerically investigated vortex shedding from various beveled trailing edges at a Reynolds number of 106. We then compared the numerical results with the experimental data, which show good agreement. We also conducted numerical simulations of wakes behind the hydrofoil at rest in periodically varying flows. Results reveal that vortex shedding is affected by the periodicity of a free-stream flow, as well as the trailing-edge shape.